A second update on mapping the human genetic architecture of COVID-19 (Matters Arising) - Kanai, Masahiro; Stevens, Christine; Neale, Benjamin M.; Daly, Mark; Demetriou, Carrie; SERRANO RUIZ, ALFREDO (My University, 2023)
.

A recent global genome-wide association study investigated the influence of host genetic factors on COVID-19 severity and susceptibility, providing valuable insights into the underlying biological pathways involved. Researchers conducted a meta-analysis using data from over 219,692 cases and 3 million controls from 35 countries. They identified 51 significant genetic loci across the entire genome associated with three phenotypes: critical illness, hospitalization, and SARS-CoV-2 infection. Of these, 46 loci remained significant after correction. The study unveiled three key biological pathways related to COVID-19 susceptibility and severity: viral entry, airway defense through mucus, and the type I interferon response. Genes involved in these pathways were identified, such as ACE2 and TMPRSS2 for viral entry and mucins in the airways for defense. Additionally, loci related to the maintenance of healthy lung tissue were identified, suggesting connections between COVID-19 severity and lung health. Genes like FOXP4, SFTPD, and MUC5B were highlighted. The study also explored genetic correlations and Mendelian randomization analyses to identify risk factors affecting COVID-19. Genetic correlations were found with smoking initiation and the number of cigarettes smoked per day, indicating a causal association with a higher risk of COVID-19. Moreover, genetically improved kidney function was associated with a reduced risk of critical illness, while genetically predicted chronic kidney disease was linked to an increased risk of severity. In summary, this study significantly expanded our understanding of host genetics in relation to COVID-19, identifying new genetic loci and providing insights into the biological pathways involved. It also underscored the importance of lung health and other risk factors in disease severity.
Artículos en revistas